Submarines in software? continuations in US software patenting in the 1980s and 1990s - Graham, Stuart J. H.; Mowrey, David C. (Economics of innovation and new technology, 2004)
This article examines the role of 'continuations' (procedural revisions of patent applications) in software patents and overall patenting in the United States during 1987-1999. The research represents the first effort of which we are aware to analyze data on continuations in software or any other patent class, providing information on the effects of 1995 changes in the US patent law intended to curb 'submarine patenting'. The analysis of all US patents shows that the use of continuations grew steadily during 1987-1995, with particularly rapid growth in software patenting. Sharp reversals in these growth rates after 1995 suggest that changes in the US patent law were effective. Prior to the 1995 changes in the patent law, continuation applications were used more intensively by large packaged-software firms than by other patentees, and both software and non-software patents subject to continuation tend to experience longer examination delays and to be more valuable.